Efficacy and safety of fremanezumab for episodic migraine prevention: Multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group trial in Japanese and Korean patients. Issue 7 (29th July 2021) - Sakai, Fumihiko; Suzuki, Norihiro; Kim, Byung‐Kun; Tatsuoka, Yoshihisa; Imai, Noboru; Ning, Xiaoping; Ishida, Miki; Nagano, Kaori; Iba, Katsuhiro; Kondo, Hiroyuki; Koga, Nobuyuki
Abstract: Objective: To evaluate the efficacy and safety of two dosing regimens of fremanezumab in Japanese and Korean patients with episodic migraine. Background: Episodic migraine, which accounts for more than 90% of migraine cases, is inadequately addressed by widely available preventive therapies. Fremanezumab, a monoclonal antibody that selectively targets the trigeminal sensory neuropeptide calcitonin gene‐related peptide involved in migraine pathogenesis, has demonstrated efficacy in international Phase 3 trials of patients with both chronic and episodic migraine. Methods: This Phase 3 randomized, placebo‐controlled trial randomly assigned patients with episodic migraine to receive subcutaneous fremanezumab monthly (225 mg at baseline, week 4, and week 8), fremanezumab quarterly (675 mg at baseline and placebo at weeks 4 and 8), or matching placebo. The primary endpoint was the mean change from baseline in the monthly average number of migraine days during the 12‐week treatment period after the first dose. Results: Of 357 patients enrolled (safety set, n  = 356; full analysis set, n  = 354), the least‐squares mean (±standard error) reductions in the average number of migraine days per month during 12 weeks were significantly greater with fremanezumab monthly (−4.0 ± 0.4, n  = 121) and fremanezumab quarterly (−4.0 ± 0.4, n  = 117) than with placebo (−1.0 ± 0.4, n  = 116; p  < 0.0001 for both comparisons). The proportion of patients reaching at least a 50% reduction in the monthly average number of migraine days during the 12‐week period after initial administration was also significantly improved with fremanezumab (fremanezumab monthly, 41.3%; fremanezumab quarterly, 45.3%; placebo, 11.2%; p  < 0.0001 for both comparisons) as were other secondary endpoints ( p  < 0.001 for all comparisons between fremanezumab and placebo). Injection‐site reactions were more common in fremanezumab‐treated patients (fremanezumab monthly, 25.6%; fremanezumab quarterly, 29.7%; placebo, 21.4%). Conclusion: Fremanezumab prevents episodic migraine in Japanese and Korean patients to a similar extent than in previously reported populations with no new safety concerns.